ARTIFICIAL INTELLIGENCE IN DENTAL HEALTH EDUCATION: INNOVATIVE SOLUTION FOR MAINTAINING DENTAL AND ORAL HEALTH - Ika Kusuma Wardani; Endah Sekar Palupi; Renie Kumala Dewi; Deby Kania Tri Putri; Rosihan Adhani; Arini Rusyda; Wianda Dewi Puspitasari; Greace Natalia Br Tarigan; A’yan Sabitah (Universitas Airlangga, 2026)
Oral health issues remain a significant public health issue in Indonesia, particularly in Barito Kuala Regency, South Kalimantan, where the prevalence of dental and oral health problems reaches 68.66%. Limited knowledge has been identified as a key contributing factor to the high prevalence of dental and oral health problems, particularly among school-aged children.This community service project aims to improve the oral health knowledge of students at MTsN 1 Barito Kuala through educational interventions using artificial intelligence (AI)-based animated video media. The activities were carried out systematically, starting from coordination with the school, student recruitment, distribution of informed consent, filling out a pre-test questionnaire, implementing the intervention, and post-intervention evaluation and data analysis. A total of 50 students participated in this activity. The pre-test results showed that 96% of students had a high level of knowledge, which increased to 98% after the intervention. The Wilcoxon test showed a significant difference (p<0.05) between the results before and after the counseling. The AI-based animated video media proved effective in improving student knowledge because it combines audio-visual elements that are appropriate for the digital learning style of today's generation. This intervention was also supported by the role of families, especially housewives, who contributed to instilling healthy dental habits. This program has the potential for sustainability through the distribution of videos on social media and the use of educational posters. The use of AI in dental health education in schools has proven to be an innovative and adaptive solution for increasing awareness and behaviors related to maintaining oral health from an early age.